EFEKTIFITAS PELAKSANAAN PIDANA MATI BANDAR NARKOBA - Muhammad Farhan Abdillah; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
The death penalty was among the most serious forms of crime in Indonesia. Not only in Indonesia, other countries far from Indonesia are also still debating the imposition of the death penalty. Drugs are dangerous substances that can damage the younger generation. Narcotics have become part of the perpetrators of drug dealers or dealers who are sentenced to death. The death penalty is considered as just since it can serve as a deterrence and can share horrors with someone who wants to commit a crime. On the other hand, the death penalty is a punishment that should not be applied because it deprives a person of the right to life. In dealing with this case, the author uses a qualitative approach. Qualitative research is understanding (understanding) social symptoms or phenomena by paying more attention to the complete picture of the phenomenon under study rather than breaking it down into related variables. According to the study's findings, the death sentence for drug-related offences should be abolished is still a criminal law enforced in Indonesia, as evidenced by the perpetrators of drug dealers and dealers of death penalty